Cytogenetics and characterization of microsatellite loci for a South American pioneer tree species, Croton floribundus - Silvestrini, Milene; Pinto-Maglio, Cecília A F; Zucchi, Maria I; dos Santos, Flavio A M (Genome, 2013)
Despite the recent advances in plant population genetic studies, the lack of information regarding pedigree, ploidy level, or mode of inheritance for many polyploids can compromise the analysis of the molecular data produced. The aim of this study was to examine both microsatellite and cytogenetic characteristics of the pioneer tree Croton floribundus Spreng. (Euphorbiaceae) to test for the occurrence of polyploidy in the species and to evaluate its implications for the appropriate use of SSR markers. Seven microsatellite markers were developed and screened for 62 individuals from a semi-deciduous tropical forest in Brazil. Chromosome number, meiotic behavior, and pollen viability were evaluated from male flower buds. All SSR loci were highly polymorphic. The number of bivalents observed in meiosis n = 56 (2n = 8× = 112) and the maximum number of alleles per individual (Ni = 8) demonstrated the occurrence of polyploidy in C. floribundus. The normal meiotic pairing and the high pollen viability suggested that C. floribundus is a regular and stable polyploid, most likely an allopolyploid. The combined SSR and cytogenetic data provided new evidence on the origin and evolution of the species as well as assured the accurate use of SSR loci for population genetic studies of the polyploid pioneer species.